Strategi Pendekatan dan Pengaruh Rusia di Kawasan Timur Tengah (2005-2019) - Mikail, Kiki (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
This study is an examination of Russia's approach and influence in the Middle East and focuses on Russia's soft politics in various Middle Eastern countries and their influence on Russian interests. The important question that will be answered in this research is how Russia can control its national interest and pressure in the Middle East geo politics. Even though after the cold war the US appeared dominant in global politics, Russia's maturity in the global political cannot be underestimated. Because Russia will continue to tightening partnerships with the countries that are anti-US dominant or at least have the same vision in global political practices including in Syria and Iran. Thus, the survival of Russia's national interest in the Middle East becomes an important factor to keep the rivalry of the two superpowers state, which is not infrequently a positive or even negative factor for the Middle Eastern countries.